2017
DOI: 10.3390/mi8060189
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Analysis and Experimental Verification of a Hybrid Vibration Energy Harvester Combining Piezoelectric and Electromagnetic Mechanisms

Abstract: Considering coil inductance and the spatial distribution of the magnetic field, this paper developed an approximate distributed-parameter model of a hybrid energy harvester (HEH). The analytical solutions were compared with numerical solutions. The effects of load resistances, electromechanical coupling factors, mechanical damping ratio, coil parameters and size scale on performance were investigated. A meso-scale HEH prototype was fabricated, tested and compared with a stand-alone piezoelectric energy harvest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 31 publications
0
35
0
Order By: Relevance
“…Based on the conclusion reported previously [21], the load resistances R1 was optimized firstly. Figure 9a plots the output power of the FUCHEH delivered to different load resistances R1 for the PEH part.…”
Section: Experiments and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the conclusion reported previously [21], the load resistances R1 was optimized firstly. Figure 9a plots the output power of the FUCHEH delivered to different load resistances R1 for the PEH part.…”
Section: Experiments and Discussionmentioning
confidence: 99%
“…Consequently, the PEH subsystem generated limited electric power; (2) the capacitive reactance of the PEH subsystem is much larger than the optimized load resistance R1 under the condition of low vibration frequency, which divided large In order to output the maximum power, the load resistances connected are optimized by experimental tests. Based on the conclusion reported previously [21], the load resistances R 1 was optimized firstly. Figure 9a plots the output power of the FUCHEH delivered to different load resistances R 1 for the PEH part.…”
Section: Experiments and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These figures are 142.18% and 122.7%, respectively, when compared with a stand-alone EM prototype. 53 An EH design that uses the TE approach, radio frequency, and vibration for wireless communication purposes generates 200 μW. 54…”
Section: Hybrid Ehmentioning
confidence: 99%
“…Figure 8e shows a combinational horizontal transducer and results showed that the downstream cylinder was inspired by both vortex-induced vibration and wake-induced vibration [75]. Xu et al [84] introduced a kind of hybrid converter using both piezoelectric effect and electromagnetic effect. It came to a result that the hybrid system works better than piezoelectric energy harvester or electromagnetic energy harvester alone.…”
Section: Miniature Energy Harvesters Of Liquid Flowmentioning
confidence: 99%